2016
DOI: 10.1097/tp.0000000000000961
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin-inhibition Results in Upregulation of Local Renin and Subsequent Vascular Endothelial Growth Factor Production in Renal Collecting Ducts

Abstract: Background Tacrolimus (Tac) and Cyclosporine A (CyA) calcineurin inhibitors (CNIs) are 2 effective immunosuppressants which are essential to prevent allograft rejection. Calcineurin inhibitors are known to be nephrotoxic. However, the precise mechanism of nephrotoxicity is not fully understood. In this study, we investigated the in vivo effects of CNIs on the local renal renin-angiotensin system in the collecting duct (CD). Methods Three-week-old mice were treated with either vehicle, CyA (2 mg/kg per day), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Recently, a study demonstrated that calcineurin inhibitors such as tacrolimus and CsA augment production of renin and vascular endothelial growth factor (VEGF) in renal collecting ducts that causes renal ischemia and periductal fibrosis resulting in calcineurin-induced nephropathy. Furthermore, this process was attenuated by aliskiren, a direct renin inhibitor that may have clinical uses in the prevention of calcineurin-induced nephrotoxicity [40]. Another recent study showed that angiotensin receptor blocker, valsartan, has beneficial effects in preventing CsA related nephrotoxicity.…”
Section: Pathophysiology Of Acute Kidney Injury In Hsctmentioning
confidence: 99%
“…Recently, a study demonstrated that calcineurin inhibitors such as tacrolimus and CsA augment production of renin and vascular endothelial growth factor (VEGF) in renal collecting ducts that causes renal ischemia and periductal fibrosis resulting in calcineurin-induced nephropathy. Furthermore, this process was attenuated by aliskiren, a direct renin inhibitor that may have clinical uses in the prevention of calcineurin-induced nephrotoxicity [40]. Another recent study showed that angiotensin receptor blocker, valsartan, has beneficial effects in preventing CsA related nephrotoxicity.…”
Section: Pathophysiology Of Acute Kidney Injury In Hsctmentioning
confidence: 99%
“…In addition, although the dose response of blood pressure to ACE inhibition is relatively flat, the antiproteinuric effect is dose dependent, particularly in populations administered calcineurin inhibitors. 9,10 It is unfortunate that Knoll et al . did not use a higher dose of ramipril in their study, as it could have important effects on the study outcome.…”
mentioning
confidence: 99%
“…Other investigators have utilized similar surgical approaches to externalize the left kidney, via left flank incision, in mice [33, 34, 35, 36, 37] and rats [35, 38, 40]. Anesthetic agent of choice for mice in some studies was intraperitoneal injection of ketamine cocktail (ketamine 100mg/kg + Xylazine 8–10mg/kg) [33, 34, 35] and Inactin, 110–130mg/kg intraperitoneal injection, was utilized for rats that underwent non-survival imaging [35, 38, 39].…”
Section: - Surgical Presentation Of Abdominal Organsmentioning
confidence: 99%
“…Anesthetic agent of choice for mice in some studies was intraperitoneal injection of ketamine cocktail (ketamine 100mg/kg + Xylazine 8–10mg/kg) [33, 34, 35] and Inactin, 110–130mg/kg intraperitoneal injection, was utilized for rats that underwent non-survival imaging [35, 38, 39]. Of note, in Rosivall’s study, for visualization of the juxtaglomerular apparatus in the mouse, a 1-mm cortical slice was removed to create a parenchymal window to expose the most superficial afferent arterioles and glomeruli [35].…”
Section: - Surgical Presentation Of Abdominal Organsmentioning
confidence: 99%
See 1 more Smart Citation